2004
DOI: 10.1039/b311009p
|View full text |Cite
|
Sign up to set email alerts
|

Singlet-oxygen generation in the catalytic reaction of dioxiranes with nucleophilic anions

Abstract: Nucleophilic anions such as Cl(-), I(-), Br(-), t-BuO(-), O(2)(-) and OH(-) efficiently catalyze the decomposition of dimethyldioxirane (DMD) and methyl(trifluoromethyl)dioxirane (TFD). Singlet oxygen ((1)O(2)) is formed in these catalytic reactions, as demonstrated by the characteristic infrared chemiluminescence (IR-CL) at 1268 nm. The yield of (1)O(2) generation, measured by the IR-CL method, lies in the range between 2 and 98%, which depends on the particular anion employed. For the bromide ion, the cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 33 publications
0
24
0
Order By: Relevance
“…Actually, there is a general tendency for a decrease in the yield of 1 O 2 in the series of anions used for the decomposition of dioxiranes (Cl --Br --I --Me 3 CO --HO -), 8,9 which is attributed to the fact that the probabili ty of the redox pathway of this reaction increases in this series. 31 According to our data, the effective catalyst pro viding a high yield of singlet oxygen should have high ionization potentials (which is equivalent to the high ЕА of the reduced state) for both catalytic forms.…”
Section: Comp -E I-d -δ R H O a R(c-h) R(hx)mentioning
confidence: 95%
See 3 more Smart Citations
“…Actually, there is a general tendency for a decrease in the yield of 1 O 2 in the series of anions used for the decomposition of dioxiranes (Cl --Br --I --Me 3 CO --HO -), 8,9 which is attributed to the fact that the probabili ty of the redox pathway of this reaction increases in this series. 31 According to our data, the effective catalyst pro viding a high yield of singlet oxygen should have high ionization potentials (which is equivalent to the high ЕА of the reduced state) for both catalytic forms.…”
Section: Comp -E I-d -δ R H O a R(c-h) R(hx)mentioning
confidence: 95%
“…It is interesting to compare the mechanism proposed in the present study with the earlier mechanistic descrip tion of the pathways of this process 8, 9 shown in Scheme 1. The important difference between the two mechanisms is the nature of the oxidized form of the catalyst and, as a consequence, the structure of the precursor of singlet oxygen (intermediate А in Scheme 1).…”
Section: Comp -E I-d -δ R H O a R(c-h) R(hx)mentioning
confidence: 96%
See 2 more Smart Citations
“…8,9 Moreover, dioxiranes belong to a new class of hyperenergetic peroxides, which produce chemiluminescence (CL) during rearrangement to the corresponding esters 8 or oxidation of organic and inorganic substrates. 10,11 In particular, the study of the dioxirane CL has led to the discovery of a new mechanism of liquid-phase organic reactions, the socalled oxygen-transfer CL. 10 Apart from dioxirane involvement, the Caro's acid-acetone system is a highly efficient source of singlet excited oxygen ( 1 O 2 ), 5 whose importance in environmental and biomedical sciences, chemi-and bioluminescence, as well as in organic synthesis, is now well recognized.…”
mentioning
confidence: 99%